Dysarthria: Definition, clinical contexts, neurobiological profiles and clinical treatments - Giulio Perrotta (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Starting from the general concept of Dysarthria, the present work focuses on the clinical, neurobiological, and functional aspects of the morbid condition, suggesting a multidimensional treatment between physiotherapy, psychotherapy, and rehabilitation exercises for lost skills.